An Assessment of Vitamin D Deficiency in Cases of Cirrhosis of Liver - Sh. Khurram Salam Sehgal, Muhammad Abdul Raziq, Jalil Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the vitamin D deficiency in cases of cirrhosis of liver at territory care hospital. Material and methods: Between April 2021 to October 2021, total 163 patients of liver cirrhosis either gender, aged 20-60 years were recruited from Department of Medicine, Sheikh Zaid Hospital, Rahim Yar Khan. Vitamin D deficiency was assessed in selected patients. Results: Total 163 patients suffering from cirrhosis of liver were recruited. Age range was 20-60 years and mean age was 38.67 ± 11.46 years. Out of 163 patients, deficiency of vitamin D was found in 76 (47%) patients. Out of 84 (51.53%) patients of age group 20-40 years and 79 (48.47%) patients of age group 41-60 years, vitamin D deficiency was found in 37 (44.05%) patients and 39 (49.37%) patients respectively in both age groups. Male patients were 59 (36.20%) and female patients were 104 (63.80%). Total 32 (54.24%) male patients and 44 (42.31%) female patients were found with vitamin D deficiency. Conclusion: Results of this study revealed that there is high proportion of deficiency of vitamin D in patients of liver cirrhosis. Most of the cirrhotic patients were between 20-40 years. Females were prominent as compared to males. CP class C was most common.